Pro ADO.NET 2.0 - Malik, Nick (Apress : Imprint: Apress, 2005)
Pro ADO.NET 2.0 is a guide and reference for .NET developers who are looking to further their understanding of ADO.NET 2.0. This book takes a new approach, focusing on the practical tasks like connecting to the database, retrieving data, and working with transactions, rather than rehashing much of the MSDN documentation. Pro ADO.NET 2.0 offers the deep and much-needed practical understanding, viewpoint, and knowledge developers are seeking. This book explains what is available in ADO.NET by associating it with the need to solve a practical problem and better architect an application, rather than mugging up the hundreds of classes and properties available in the framework.